Thermodynamic insights and assessment of the 'circular economy'. (20th September 2017) - Cooper, Samuel J.G.; Giesekam, Jannik; Hammond, Geoffrey P.; Norman, Jonathan B.; Owen, Anne; Rogers, John G.; Scott, Kate
Abstract: This study analyses the effect on energy use of applying a wide range of circular economy approaches. By collating evidence on specific quantifiable approaches and then calculating and analyzing their combined full supply chain impacts through input-output analysis, it provides a more complete assessment of the overall potential scope for energy savings that these approaches might deliver than provided elsewhere. Assessment is conducted globally, across the EU-27 and in the UK. Overall, the identified opportunities have the potential to save 6%–11% of the energy used to support economic activity, worldwide and in the EU, and 5%–8% in the UK. Their potential is equivalent to the total scope for other industrial energy efficiency savings. The potential savings are further divided into those due to sets of approaches relating to food waste, steel production, other materials production, product refurbishment, vehicle provision, construction and other equipment manufacture. Each of these sets of approaches can make a key contribution to the total savings that are possible. Complementary use of energy and exergy metrics illustrates the way in which energy use might change and for the first time provides indication that in most cases other energy efficiency measures are unlikely to be adversely affected by the circular economy approaches. Potential for savings in the energy embodied in each key product input to each major sector is assessed, enabling prioritization of the areas in which the circular economy approaches have the greatest scope for impact and identification of supply chains for which they are underrepresented. Highlights: Circular economy approaches could reduce energy use in economic activity by 6%–11%. Energy savings complement energy efficiency approaches and equal their potential. Large potentials in food waste, material efficiency, refurbishment and construction. Potential benefits enhanced by widespread (level and location) adoption of approaches.